2022
DOI: 10.1002/msd2.12051
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid multibody system method for the dynamic analysis of an ultra‐precision fly‐cutting machine tool

Abstract: The dynamics of an ultra‐precision machine tool determines the precision of the machined surface. This study aims to propose an effective method to model and analyze the dynamics of an ultra‐precision fly‐cutting machine tool. First, the dynamic model of the machine tool considering the deformations of the cutter head and the lathe head is developed. Then, the mechanical elements are classified into M subsystems and F subsystems according to their properties and connections. The M‐subsystem equations are formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Chen and Zhao first developed a theoretical model to extract relative tool‐workpiece vibration from the machined surface and used this model to predict the surface roughness in SPDT. Recently, some researchers have investigated the dynamic modeling of UPFC and its impact on surface roughness generation, specifically taking tool‐tip vibration into account 11,16–20 . Ding et al 16 developed a dynamic model of the UPFC machine tool using the transfer matrix method for multibody system (MSTMM) 21 and simulated the tool‐tip vibration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen and Zhao first developed a theoretical model to extract relative tool‐workpiece vibration from the machined surface and used this model to predict the surface roughness in SPDT. Recently, some researchers have investigated the dynamic modeling of UPFC and its impact on surface roughness generation, specifically taking tool‐tip vibration into account 11,16–20 . Ding et al 16 developed a dynamic model of the UPFC machine tool using the transfer matrix method for multibody system (MSTMM) 21 and simulated the tool‐tip vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al 19 extended their previous work using a hybrid method consisting of MSTMM, the FEM, and the Craig–Bampton reduction method. The authors' investigation revealed that two specific mode shapes played a critical role in the vibration of the tool‐tip, ultimately leading to the pronounced waviness observed on the machined surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploration of methods for modeling kinetostatic and dynamic behaviors of compliant mechanisms and rigid‐body mechanical systems has been an interesting technological subject though software packages are commercially available 1–6 . A process‐efficient, result‐accurate, and parameter‐insightful modeling methodology is often desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with series manipulators, parallel manipulators have the advantages of high precision, high speed, and strong load capacity [1]. Therefore, they are widely used in precision manufacturing [2], automatic microassembly [3], surgical robots [4], and other applications. As the speed and acceleration of the rigid manipulator are limited, some scholars have proposed and designed lightweight manipulators that use flexible components instead of the original rigid components.…”
Section: Introductionmentioning
confidence: 99%